Penerapan E-Business Dalam Rangka Memajukan Strategi Pemasaran Produk UMKM - Umi Afifah Yeni Asari; Puji Astutik; Novi Ariyanti; Ratna Nindiya Agustina; Indah Parwati (Academica: Journal of Multidisciplinary Studies, 2022)
Micro, Small and Medium Enterprises (MSMEs) play an important role in the Indonesian economy.  However, marketing problems are the main obstacle for the MSME business at this time, the marketing system which is still traditional in nature makes it difficult for MSME businesses to spread their wings to various regions.  This study aims to find out how far people understand E-Business and find out whether E-Business can attract consumer interest and help market products to a wider realm.  The method used in this research is qualitative method.  The data collection technique is by in-depth interviews with one of the MSME business actors in the villages of Wungusari, Tegaldowo, Gemolong, Sragen directly and literature studies, then the results of the interviews are stored in recorded form and transcribed completely.  The results obtained are that public knowledge about E-Business is still very lacking and this is due to the lack of education to several MSME business actors and the public as consumers.  E-Business can help marketers attract consumer interest and make it easier for consumers to get the products they want, besides that E-Business also makes it easier for MSME business players to market their products widely to various regions and even between countries.  So it can be concluded that the application of E-Business can provide great opportunities for MSME businesses in developing their products and assisting MSME businesses in increasing income both locally and nationally. Keywords: E-Business; Marketing; MSME